Antara Teks dan Realitas : Analisis Hadist Pernikahan Beda Agama dalam Konteks Pluralisme di Indonesia - Ulinnuha Abdurrahman; Masruhan Masruhan; Nurlailatul Musyafaah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Marriage is a crucial social and religious institution in Indonesia's plural society, where Islamic Sharia strongly emphasizes the importance of shared faith (aqidah) between spouses. Normatively, the Qur’an and hadiths provide strict limitations on the practice of interfaith marriage due to concerns about serious problems in aspects of worship, child education, and the integrity of the family's faith. In the context of Indonesian positive law, although Law No. 1 of 1974 states that the validity of marriage depends on respective religious laws, there was briefly a legal loophole allowing the registration of interfaith marriages, which was subsequently affirmed closed by the Supreme Court. This article examines this issue through Normative Legal Research using a philological approach to the Prophet’s hadiths such as the story of Sayyidah Zainab and the athar (narration) from Ibn Umar and linking it to the context of pluralism and positive law in Indonesia. The analysis shows that the provision in the hadith about the marriage of Sayyidah Zainab and Abu al-‘Ash was abrogated (mansukh) after the revelation of the verses Al-Baqarah 221 and Al-Ma’idah 5, and the athar of Ibn Umar affirms the prohibition of marrying women of the People of the Book, reflecting a spirit of caution in safeguarding family faith. The results of this study affirm that both Islamic Sharia and state law especially through SEMA No. 2 of 2023 are aligned in rejecting interfaith marriage. Thus, pluralism in Indonesia is interpreted as affirming peaceful coexistence without sacrificing one's religious identity, making interfaith marriage a theological, legal, and socio-cultural problem that must be avoided.